ISSUES AMONG NOVICE TEACHERS IN MALAYSIA - Sofiah Zakaria; Khaliza Saidin; Rozi Mohamad (Proceedings of The ICECRS, 2016)
Issues and problems faced by novice teachers have long been questions of great interest in the field of education and are still receiveing considerable critical attention amongst players in the field. Hence, this study seeks to explore the issues and problems faced by novice teachers. Qualitative content analysis was used to examine 13 local journal articles written on the subject of novice teachers from 2006 to 2015. Data were then grouped into themes to identify issues and problems faced by novice teachers. Findings of this study showed that issues faced by novice teachers include issues related to efficacy, classroom and student behaviour management, professional development, competency, commitment, stress, and support among novice teachers. Based on the findings, more studies on mentoring aspect should be carried out to assist novice teachers to start off their teaching career and provide them with necessary emotional and motivational support to improve their teaching in schools.